1997
DOI: 10.1002/(sici)1099-0739(199709)11:9<707::aid-aoc632>3.3.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Organometallic complexes with biological molecules. IX. Diorgano- and triorgano‐tin(IV)[meso‐tetra (4-sulfonatophenyl)porphinate] derivatives: solid‐state and solution‐phase structural aspects and in vivo effects

Abstract: Diorgano-and triorgano-tin(IV) derivatives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 34 publications
3
17
0
Order By: Relevance
“…In this context, we regarded a class of porphyrin derivatives as potential anti-tumor drugs for their cytotoxicity and for the property of the porphyrins themselves to be accumulated in large amounts and retained for prolonged periods of time by the malignant lesions as noteworthy (3)(4)(5). We showed that two complexes of the meso-tetra(4-sulfonatophenyl) porphinate (TPPS), (Bu 2 Sn) 2 TPPS and (Bu3Sn)4TPPS, induce the activation of extrinsic and intrinsic apoptotic pathways in melanoma cells (6).…”
Section: Introductionsupporting
confidence: 58%
“…In this context, we regarded a class of porphyrin derivatives as potential anti-tumor drugs for their cytotoxicity and for the property of the porphyrins themselves to be accumulated in large amounts and retained for prolonged periods of time by the malignant lesions as noteworthy (3)(4)(5). We showed that two complexes of the meso-tetra(4-sulfonatophenyl) porphinate (TPPS), (Bu 2 Sn) 2 TPPS and (Bu3Sn)4TPPS, induce the activation of extrinsic and intrinsic apoptotic pathways in melanoma cells (6).…”
Section: Introductionsupporting
confidence: 58%
“…Moreover, Girard et al (2000) obtained toxic effects on larval survival and growth of P. lividus larvae after exposure of eggs to 0.03-0.3 lg l )1 of TBT, suggesting that concentrations of TBT with no effect on the embryonic development could affect the sea urchin larval cycle and metamorphosis. Organoestanic compounds like TBT have been found to damage the embryonic and larval development of Ciona intestinalis in the 0.1-10 lM concentration range (Mansueto et al, 1993a, b;Maggio et al, 1994;Gianguzza et al, 1996;Pellerito et al, 1997Pellerito et al, , 1998Mansueto et al, 2000). In contrast, our results showed toxic effects of TBT at concentrations of a nanomolar range (EC 50 = 22 nM), although the incubation times in our toxicity tests are higher (20 h).…”
Section: Discussionmentioning
confidence: 99%
“…Their solid state and solution configurations were reported, together with their in vivo cytotoxic activity [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the biological effects of organotin(IV) derivatives have been the focus of research in embryos and gametes of Ascidians [7,10,11]. Furthermore, attention has been addressed on the interaction with DNA of newly synthesized compounds [6,10,12] and on the antineoplastic effect of several organotin(IV) compounds [13][14][15].…”
Section: Introductionmentioning
confidence: 99%